ANALISIS KETERAMPILAN ABAD 21 PADA PEMBELAJARAN TEMATIK - Rindiani; Nurhasanah, Ana; Alamsyah, Trian Pamungkas (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2022)
This research is based on the urgency of the challenge for teacher in creating a mature learning plan so that it can produce students who are superior and able to compete by developing 21st century skills. The purpose of this research is to describe the utilization of facilities and infrastructure to support learning activities in the 21st century, the implementation process, and the results of learning activities that focus on 21st century skills which include 4C skills (critical thinking, creativity, collaboration, and communication) in thematic learning in class V SDN Sumampir. This research uses a qualitative approach and descriptive method. The subjects in this study were class V teachers and 30 students. Through data collection techniques triangulation techniques such as interviews, observation, and documentation, using the Miles and Huberman analysis model, which consists of the process of data presentation, and verification/conclusion drawing. The results of this study indicate that the utilization of facilities and infrastructure to support 21st century leaning activities at SDN Sumampir is not optimal enough due to the limited number, grade V teachers have implemented 21st century skills in learning activities with their teaching skills, and grade V students have been optimal in applying 4C skills in thematic learning activities.